Natural Musicality Explains Unique Variance in Children’s Reading Fluency - Martins, M. (The Neurosciences and Music VIII, 2024)
It is widely assumed that musical abilities and reading are linked. Most studies focused on the effects of deliberate musical practice in lower-level reading processes, such as phonological awareness and single-word reading, and restricted musical abilities to musical perceptual skills. On natural musicality — musical abilities and behaviors that may result from genetic predisposition and/or informal experience — and on more ecologically valid reading measures, such as reading fluency, there is limited evidence. Here, we asked whether natural musicality, as measured by task-based performance and teachers’ reports, explains unique variance in reading fluency of early readers after accounting for demographic, socioeconomic, and cognitive contributions. One hundred and twenty-one elementary school children (64 girls; M age = 8.53, SD = 1.12) participated in this study. Children were musical naïve (i.e., they had no prior musical training) and performed tasks on musical auditory perception, reading fluency and general cognition; teachers reported on children’s musicality and parents on their sociodemographic characteristics. A hierarchical linear regression showed that musicality, as measured by task-based performance and teachers’ reports, predicted unique variance in reading fluency after accounting for age, sex, parental education, family’s income and general cognition. When the teachers’ report of children’s musicality was considered separately in the model, it explained additional variance to that accounted for task-based performance. These findings support a fundamental link between natural musicality (musical abilities and behaviors) and reading, and this should be considered in studies inspecting musical training benefits on reading. They also suggest that musicality cannot be narrow to musical auditory perception, and, thus, future studies on music and related effects should adopt a more comprehensive approach to assess musical ability and behaviors.